1969
DOI: 10.1901/jeab.1969.12-1049
|View full text |Cite
|
Sign up to set email alerts
|

PERSISTENT SHOCK‐ELICITED RESPONDING ENGENDERED BY A NEGATIVE‐REINFORCEMENT PROCEDURE1

Abstract: A procedure in which responses reduced intermittently presented electric shocks to one quarter of their originally scheduled intensity, effectively engendered and maintained lever pressing in hooded rats. This contingency also markedly increased the response rates of rats initially trained under an unsignaled avoidance procedure. The responding of all animals extinguished rapidly when shock was withdrawn. Subsequently, it was discovered that high response rates could be maintained solely through presentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 18 publications
2
17
0
1
Order By: Relevance
“…Badia and Culbertson (1972) An unexpected observation was that, under the control treatment, three of four subjects increased in the per cent of time allocated to the alternate condition, apparently as a function of repeated exposures to the experimental treatment. Powell and Peck (1969) reported a similar finding after bar pressing had been reinforced by shock-intensity reductions. The bar pressing was maintained by response-inidependent shocks in control proceduires when the intensity of shock was not reduced.…”
Section: Discussionmentioning
confidence: 54%
“…Badia and Culbertson (1972) An unexpected observation was that, under the control treatment, three of four subjects increased in the per cent of time allocated to the alternate condition, apparently as a function of repeated exposures to the experimental treatment. Powell and Peck (1969) reported a similar finding after bar pressing had been reinforced by shock-intensity reductions. The bar pressing was maintained by response-inidependent shocks in control proceduires when the intensity of shock was not reduced.…”
Section: Discussionmentioning
confidence: 54%
“…Results of other studies have shown response maintenance under noncontingent shock presentation (e.g., Herrnstein & Hineline, 1966;Kelleher, Riddle, & Cook, 1963). For example, Powell and Peck (1969) trained rats under conditions in which responding reduced the intensity of scheduled shocks but did not terminate or postpone shock. The subjects were then exposed to a noncontingent shock condi-tion in which responding had no effect on either shock intensity or frequency.…”
Section: Noncontingent Presentation and Removal Of Aversive Stimulimentioning
confidence: 95%
“…In fact, a few researchers have used punishment to produce reductions in responding maintained by negative reinforcement. For example, Powell and Peck (1969) found that rats trained under a procedure in which responding reduced the intensity of scheduled shocks continued to respond under a noncontingent-shock condition in which responding did not influence the schedule or intensity of shock. However, responding was reduced when each response resulted in additional shock.…”
Section: Contingency Reversalsmentioning
confidence: 99%
“…Shock-elicited aggression might produce, for example, postshock response bursting during free-operant avoidance (e.g., Sidman, 1958) and the extreme persistence of responding sometimes noted when shocks are delivered during the extinction of avoidance behavior (e.g., Herrnstein and Hineline, 1966;Powell and Peck, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…But, by the nature of his procedure, his subjects were undoubtedly near the escape lever immediately after a shock, and thus would have been more likely to attack that lever than the other one. Powell and Peck (1969) found that a procedure in which intermittently scheduled shocks were reduced in intensity (but not avoided) by lever-press responses markedly increased the response rates of rats initially trained under a free operant avoidance procedure. They also found that high response rates could be maintained solely through the presentation of shocks that were not affected by responses.…”
mentioning
confidence: 96%